Sultan Abu Bakar's Foreign Guests and Travels Abroad, 1860s-1895: Fact and Fiction in Early Malay Historical Accounts - A Rahman Tang Abdullah (Malaysian Branch of the Royal Asiatic Society, 2011)
Much has been written about the foreign travels of Sultan Abu Bakar of Johor (r.1862-1895). A comparison of the various versions reveals that early Malay accounts of these foreign trips tended to be uncritical, fragmentary, partial, to praise and glorify him unreservedly, to invent and exaggerate facts, while contemporary non-Malay accounts, especially those written in English, were more rounded, comprehensive, and objective and included detailed facts, comments and criticisms on his extensive travels, lifestyle and his yearning for recognition. This paper intends to unravel fact from fiction in the Malay accounts, especially those written in the form of the Malay long poem, the syair, about his private and official life. It will also examine to what extent the early Malay accounts still reflected features of traditional Malay historiography, and critically evaluate Abu Bakar's reception of foreign guests in Johor and his observance of Islamic practice and Malay tradition at social functions, which have not previously been raised by other scholars.